2007
DOI: 10.1002/cncr.22394
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and discriminating three‐risk‐group prognostic scoring system for staging Hodgkin lymphomas

Abstract: BACKGROUND.Several 3‐stage Ann Arbor classification‐derived prognostic systems were constructed since 1980 to identify the prognosis of Hodgkin lymphoma (HL). Modern statistical tools were applied to 955 patients treated between 1981 and 1996 to build a 3‐stage prognostic scoring system (PSS).METHODS.Each variable associated with 10‐year overall survival (10‐year OS) was assigned to 2 (0 or 1) or 3 (0, 1 or 3) values. By summing the values attributed to each variable, 3 stages were defined. 10‐year OS, 5‐year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…[2][3][4]21,22 Recent studies of prognostic scoring systems for adult HL have not identified BM involvement as a significant predictor of outcome 18,23 and have not included it in the prognostic scoring system. 18,23,24 In previous pediatric studies, the incidence of BM involvement at diagnosis ranged from 1.8% to 6.5%. [7][8][9] In our study, the incidence was 5.5% in the whole cohort.…”
Section: Discussionmentioning
confidence: 95%
“…[2][3][4]21,22 Recent studies of prognostic scoring systems for adult HL have not identified BM involvement as a significant predictor of outcome 18,23 and have not included it in the prognostic scoring system. 18,23,24 In previous pediatric studies, the incidence of BM involvement at diagnosis ranged from 1.8% to 6.5%. [7][8][9] In our study, the incidence was 5.5% in the whole cohort.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to other risk scores, the four variables in the prognostic scoring system that were associated with poorer overall survival did not include male gender, but did include age, number of involved lymphoid areas, visceral disease, and B-symptoms. 9 None of the above mentioned prognostic scores allow an individual's risk profile to be determined before or during treatment. Furthermore, prognostic factors determined in the past gradually lose their predictive power as treatment is successfully adapted to the disease burden.…”
Section: Gender As a Prognostic Factor For Patients With Hodgkin Lympmentioning
confidence: 99%
“…1 It is important to note that the median followup of this large group of patients exceeded 10 years and by 5 years no patient had been lost to follow-up. The size of the patient sample, as well as its extensive follow-up, enabled us to obtain stable and reliable 10-year survival and 5-year event-free survival (EFS) probabilities.…”
Section: Author Replymentioning
confidence: 87%